If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 173 Solving 7 + -3x = 173 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 173 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 173 + -7 -3x = 173 + -7 Combine like terms: 173 + -7 = 166 -3x = 166 Divide each side by '-3'. x = -55.33333333 Simplifying x = -55.33333333
| (6x-4)-8=12 | | -3=-4+5a-4a | | 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= | | 6(1x-1x)=11x-2(x+2) | | 7.2-3y=5 | | 5r-5r=1 | | 7.1-3y=5 | | 5.2+y=10 | | 3x+2x-20+4x-20=180 | | 5.1+y=10 | | -49x^2+6=-7x | | 5v-2v=-24 | | -4-n-4n+15=0 | | 9y+9-9y=18-9y | | 5x^2-110x+105= | | -5x+15=7x-21 | | 7-3y=5 | | 1/2(10-2)-1/6(60-5) | | 0.5x+0.83=0.66x-0.25 | | -5(x-3)=7(x-3) | | 22p+2p+p= |